Salivary spectral signature using ATR-FTIR spectroscopy in different exercise protocols - de Souza, Adriele Vieira; Teixeira, Renata Roland; Caixeta, Douglas Carvalho; Silva, Alinne Tatiane Faria; Gonçalves, Luis C.O.; Giolo, Jéssica Sanjulião; Vilela, Danielle Diniz; Peixoto, Leonardo Gomes; Magalhães-Neto, Anibal M; Maia, Yara Cristina Paiva; Sabino-Silva, Robinson; Puga, Guilherme Morais; et al. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2024)
[Display omitted] •The salivary spectrum pattern of continuous exercise (CE) closely resembled that of high-intensity interval exercise (HIEE), whereas resistance exercise (RE) showed minor alterations.•The spectral wavenumbers identified by FTIR could serve as effective markers in distinguishing between different exercise modalities, with sensitivity, specificity, and accuracy, correlating with the metabolic changes induced by exercise. The Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR-FTIR) has been applied to determine salivary biomarkers with high sensitivity and cost-effectiveness. Our study aimed to test the hypothesis that the spectral profile of saliva demonstrates distinct vibrational modes corresponding to different exercise protocols, thereby facilitating exercise monitoring. Saliva samples were collected from trained male subjects at three intervals: pre-exercise, post-exercise, and 3 h post-exercise. The protocols included acute sessions of continuous exercise (CE), high-intensity interval exercise (HIIE), and resistance exercise (RE). ATR-FTIR analysis revealed that salivary biochemical components changed uniquely with each exercise protocol. Specific spectral vibrational modes were identified as potential biomarkers for each exercise type. Notably, the salivary spectrum pattern of CE closely resembled that of HIIE, whereas RE showed minor alterations. Furthermore, we attempted to apply an algorithm capable of distinguishing the spectral range that differentiates the exercise modalities. This pioneering study is the first to compare changes in saliva spectra following different exercise protocols and to suggest spectrum peaks of vibrational modes as markers for specific types of exercises. We emphasize that the spectral wavenumbers identified by FTIR could serve as practical markers in distinguishing between different exercise modalities, with sensitivity, specificity, and accuracy correlating with the metabolic changes induced by exercise. Therefore, this study contributes a panel of ATR-FTIR spectral wavenumbers that can be referenced as a spectral signature capable of distinguishing between resistance and endurance exercises.